Exposure to anti-seizure medication during pregnancy and the risk of autism and ADHD in offspring: a systematic review and meta-analysis - Xu, Shan-Chun; Zhong, Ying; Jiang, Hai-Yin; Tang, Jun (Frontiers in Neurology, 2024)
Background: Evidence of an association between maternal use of anti-seizure medication (ASM) during pregnancy and the risk of autism spectrum disorder (ASD) or attention-deficit/hyperactivity disorder (ADHD) in children is conflicting. This systematic review and meta-analysis aimed to summarise the relationship between foetal exposure to ASM and the development of ASD or ADHD in offspring. Methods: A comprehensive literature search was conducted in PubMed and other databases to identify relevant epidemiological studies published from inception until 1 March 2024. Results: Seven cohort studies were included in the meta-analysis. The results showed that maternal exposure to ASMs during pregnancy was associated with an increased risk of ASD (odds ratio [OR]: 2.1, 95% confidence interval [CI]: 1.63–2.71; P < 0.001) in the general population. This association became weaker (ASD: OR: 1.38, 95% CI: 1.11–1.73; P = 0.004) when the reference group was mothers with a psychiatric disorder or epilepsy not treated during pregnancy. Furthermore, an increased risk of ADHD was observed when the study data adjusted for drug indications were pooled (OR: 1.43, 95% CI: 1.07–1.92; P = 0.015). In subgroup analyses based on individual ASM use, only exposure to valproate preconception was significantly associated with an increased risk of ASD or ADHD. Conclusions: The significant association between maternal ASM use during pregnancy and ASD or ADHD in offspring may be partially explained by the drug indication or driven by valproate.